The role of ethical standards in technological innovation - BARHOUM , Nesrine; BOUDABBOUS , Sami (Revue Internationale des Sciences de Gestion, 2025)
This research focuses on the complex relationship between organizational ethics and technological innovation, a highly relevant topic in a context marked by accelerated digitalization and increasing demands for social responsibility. The interest of this study lies in understanding how ethical dimensions, often perceived as constraints, can instead become levers for sustainable innovation. To address this issue, a quantitative approach based on structural equation modeling (SEM-PLS) was used to analyze the influence of ethical obstacles and ethical norms on technological innovation. The data, collected from a sample of organizational stakeholders, allowed for the validation of the reliability and consistency of the measures through various statistical tests. The results reveal that ethical obstacles have a negative and significant effect on innovation, while ethical norms have a very strong positive effect. These conclusions suggest that ethics, when institutionalized in the form of clear and shared principles, becomes a driver of responsible innovation and sustainable performance, while ethics perceived as overly restrictive can hinder creativity and risk-taking.